2018
DOI: 10.1186/s13054-018-2079-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompromised patients with acute respiratory distress syndrome: secondary analysis of the LUNG SAFE database

Abstract: BackgroundThe aim of this study was to describe data on epidemiology, ventilatory management, and outcome of acute respiratory distress syndrome (ARDS) in immunocompromised patients.MethodsWe performed a post hoc analysis on the cohort of immunocompromised patients enrolled in the Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure (LUNG SAFE) study. The LUNG SAFE study was an international, prospective study including hypoxemic patients in 459 ICUs from 50 countries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 36 publications
(39 reference statements)
6
72
1
9
Order By: Relevance
“…The involvement of immune cells, including neutrophils [6,7] lymphocytes [8], and regulatory T-cell [9,10], has become an active topic of research in ARDS pathogenesis. To date, few clinical studies on the immune status of ARDS patients have focused on aetiology, treatment and prognosis [11]. Immunocompromised individuals represent a significant proportion of ARDS patients [11,12], these patients do not have the ability to respond normally to an infection due to an impaired or weakened immune system.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of immune cells, including neutrophils [6,7] lymphocytes [8], and regulatory T-cell [9,10], has become an active topic of research in ARDS pathogenesis. To date, few clinical studies on the immune status of ARDS patients have focused on aetiology, treatment and prognosis [11]. Immunocompromised individuals represent a significant proportion of ARDS patients [11,12], these patients do not have the ability to respond normally to an infection due to an impaired or weakened immune system.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…To date, few clinical studies on the immune status of ARDS patients have focused on aetiology, treatment and prognosis [11]. Immunocompromised individuals represent a significant proportion of ARDS patients [11,12], these patients do not have the ability to respond normally to an infection due to an impaired or weakened immune system. Some studies have shown that ARDS occurs in patients with previous immunodeficiencies, such as haematologic malignancies, active solid tumours, solid organ transplantation, and acquired immunodeficiency syndrome, as well as in patients taking long-term or high-dose corticosteroids or immunosuppressants, and those who use extra-corporeal membrane oxygenation (ECMO) may have a better prognosis [13].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive ventilation (NIV) is frequently used as firstline respiratory support in HSCT patients [46]. However, early studies which showed a mortality benefit in immunosuppressed patients with using NIV compared to invasive mechanical ventilation were limited by relatively few numbers of HSCT patients and extremely high mortality in the control groups [47,48].…”
Section: Respiratory Viral Infection Is Common Aftermentioning
confidence: 99%
“…In this patient the pattern of infection by Pneumocystis jiroveci, Staphylococcus aureus/MSSA, Candida dubliniensis, Cytomegalovirus and Legionella pneumophila reflecst the compromised immune function. The mortality of immunosuppressed patients suffering ARDS is increased [1] regardless of the severity of the disease. Polimicrobial infections are seen regularly in immunocompromised critically ill patients.…”
Section: Introductionmentioning
confidence: 99%